Domestic Violence and Its Impact on Abortion in Iran: Evidence From a Nationally Representative Survey - Bagheri, Reyhaneh (Journal of interpersonal violence, 2023)
The objective of this article is to assess the effect of domestic violence on abortion and investigate the mediating role of unwanted pregnancy. A secondary analysis was conducted on the National Family Survey data. This survey was a cross-sectional study conducted across Iran in 2018. The association between domestic violence and abortion was analyzed using the Partial Least Square-Structural Equation Model (PLS-SEM) with WarpPLS version 8.0. From among 1,544 married women (mean age 42.8 years) who participated in this survey, 27% (418 women) reported experiencing at-least one-lifetime of abortion. Overall, two in three women (67.3%) experienced at least one form of domestic violence. Almost half of the women with experience of abortion (49.3%) reported at least one unwanted pregnancy in their life course. The bivariate analysis showed a significant positive relationship between domestic violence and abortion, and there was a positive direct effect of domestic violence on unwanted pregnancy. Moreover, age had a negative direct and indirect effect on unwanted pregnancy and abortion. Although, the direct effect of domestic violence on abortion was not significant in the Structure Equation Model, a positive indirect effect of domestic violence on abortion through unwanted pregnancy was confirmed. The effect of unwanted pregnancy on abortion was particularly strong (β = .395, p < .01). These results have some implications for prevention of abortion through interventions against unwanted and unplanned pregnancy and domestic violence. This study makes a unique theoretical contribution to the literature through assessing the mediating role of unwanted pregnancy between domestic violence and abortion by using the SEM model.